Proceedings of the 15th European Conference on Research Methodology for Business and Management Studies : ECRM 2016 9-10th June 2016 : hosted by Kingston Business School, Kingston University London, UK /: ECRM 2016 9-10th June 2016 : hosted by Kingston Business School, Kingston University London, UK. ([2016]) - Unknown
No abstract available